Effect of prone positioning on end-expiratory lung volume, strain and oxygenation change over time in COVID-19 acute respiratory distress syndrome: A prospective physiological study - Dilken, Olcay; Rezoagli, Emanuele; Yartaş Dumanlı, Güleren; Ürkmez, Seval; Demirkıran, Oktay; Dikmen, Yalım (Frontiers in Medicine, 2022)
Abstract Background: Prone Position (PP) is a recommended intervention in severe classical Acute Respiratory Distress Syndrome (ARDS). Changes in lung resting volume, respiratory mechanics and gas exchange during a 16-hour cycle of PP in COVID-19 ARDS has not been yet elucidated. Methods: Patients with severe COVID-19 ARDS were enrolled between May and September 2021 in a prospective, cross-over, physiological study in a University Teaching Hospital. Lung resting volume was quantitatively assessed by multiple breath nitrogen wash-in/wash-out technique to measure the End-Expiratory Lung Volume (EELV). Timepoints included the following: Baseline, Supine Position (S1); start of PP (P0), and every 4-hour (P4; P8; P12) until the end of PP (P16); and Supine Position (S2). Respiratory mechanics and gas exchange were assessed at each timepoint. Measurements and Main Results: 40 mechanically ventilated patients were included. EELV/Predicted Body Weight (PBW) increased significantly over time. The highest increase was observed at P4. The highest absolute EELV/PBW values were observed at the end of the PP (P16 vs S1; median 33.5 ml/kg [InterQuartileRange, 28.2-38.7] vs 23.4 ml/kg [18.5-26.4], p<0.001). Strain decreased immediately after PP and remained stable between P4 and P16. PaO2/FiO2 increased during PP reaching the highest level at P12 (P12 vs S1; 163 [138-217] vs 81 [65-97], p<0.001). EELV/PBW, strain and PaO2/FiO2 decreased at S2 although EELV/ PBW and PaO2/FiO2 were still significantly higher as compared to S1. Both absolute values over time and changes of strain and PaO2/FiO2 at P16 and S2 versus S1 were strongly associated with EELV/PBW levels. Conclusions: In severe COVID-19 ARDS, EELV steadily increased over a 16-hour cycle of PP peaking at P16. Strain gradually decreased, and oxygenation improved over time. Changes in strain and oxygenation at the end of PP and back to SP were strongly associated with changes in EELV/PBW. Whether the change in EELV and oxygenation during PP may play a role on outcomes in COVID-ARDS deserves further investigation.